1995
DOI: 10.1254/jjp.67.51
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Myocardial Infarction Model in the Rat and Its Properties

Abstract: ABSTRACT-The photochemical reaction between rose bengal and light (540 nm) produces thrombotic occlusion in rat coronary artery. We have now developed an experimental myocardial infarction (MI) model by photochemically induced thrombosis (PIT) in rats and investigated the mechanisms responsible for the induction of MI. PIT in the coronary artery induced myocardial ischemia, which was determined by tissue oxygen tension (tpO2), and resulted in MI. Pretreatment with a thromboxane (TX) A2-receptor antagonist, vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
(24 reference statements)
0
8
0
1
Order By: Relevance
“…Administrations of TP receptor antagonists inhibit the vasoconstrictor actions of isoPs, which suggest an activation of either a TP receptor or a TP receptor like isoP receptor [1,2,35]. Although the use of TP-receptor antagonists in experimental studies reduced myocardial infarctions and dysfunctions [36][37][38], similar results of clinical studies, to our knowledge, are yet outstanding. In contrast, the beneficial effects of EPA and DHA had been proven in numerous experimental and clinical studies [10,11,21,22,39].…”
Section: Discussionmentioning
confidence: 86%
“…Administrations of TP receptor antagonists inhibit the vasoconstrictor actions of isoPs, which suggest an activation of either a TP receptor or a TP receptor like isoP receptor [1,2,35]. Although the use of TP-receptor antagonists in experimental studies reduced myocardial infarctions and dysfunctions [36][37][38], similar results of clinical studies, to our knowledge, are yet outstanding. In contrast, the beneficial effects of EPA and DHA had been proven in numerous experimental and clinical studies [10,11,21,22,39].…”
Section: Discussionmentioning
confidence: 86%
“…Contractile synergism between 5-hydroxytryptamine and other vasoconstrictor substances has been observed in a number of peripheral and cerebrovascular blood vessels (19). In some animal coronary artery models (20,21), as well as in human coronary arteries (22,23), a contractile synergistic effect between 5-hydroxytryptamine and U46619 has been demonstrated.…”
Section: Discussionmentioning
confidence: 98%
“…Several rat models of arterial thrombotic occlusion have been described, 19,25,26 including the photochemical injury model, which has been applied to several arterial beds, namely, the femoral artery, 26 coronary artery, 16 middle cerebral artery, 20 and carotid artery. 27 In this study, we utilized this approach to examine the effects of P2Y 12 inhibition on MI after thrombotic coronary artery occlusion originally described by Hirata et al 16 Prasugrel (3 mg/kg, po) demonstrated near-complete inhibition of P2Y 12 but resulted in an approximately 60% inhibition of infarct size, suggesting only a partial role for P2Y 12 in this thrombotic model of MI.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation with green light (F: 3 mm) was achieved by using a xenon lamp (L4887: ;60,000 lx, Hamamatsu Photonics, Hamamatsu). 16 The head of the green light source was fixed under the left atrium, and rose bengal (20 mg/kg) was administered. The green light was applied to an area including the junction of the left circumflex artery and left anterior descending artery for 30 minutes.…”
Section: Induction Of Myocardial Infarction By Photochemical Irradiatmentioning
confidence: 99%